TINJAUAN MODEL GOMS APLIKASI MEGA DALAM INTERAKSI MANUSIA DAN KOMPUTER - Nabil, Pratama Syahdan; Anshori, Iedam Fardian (Universitas PGRI Semarang, 2021)
Human Computer Interaction (Human Computer Interaction) is a discipline that teaches and studies communication or interaction between users and systems. In human computer interaction, there are several models, one of which is the GOMS model. The GOMS model itself is an original approach to an evaluation-based model in the field of computer user interfaces. in this study, we conducted a review of an application called Mega. Mega application is a cloud storage application and file hosting service offered by Mega company. Our review aims to see and find out what the GoMS model is and see what impact it has on applications that use it. From this research, we know that the GOMS model provides convenience and effectiveness in the application